PERAN JERAMI PADI DALAM MEMPERBAIKI HASIL GABAH DAN SERAPAN KALIUM DI LAHAN SAWAH TADAH HUJAN DI KABUPATEN PATI, JAWA TENGAH - A Wihardjaka (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2015)
As agricultural waste, rice straw could be used to substitute potassium fertilizer in food crops farming system, especially rice crop. The use of rice straw in rainfed lowland areas is not significant to substitute potassium fertilizer which is relatively higher cost. The field experiment was conducted to determine potassium uptake pattern of rainfed lowland rice in light textural Endoaquepts through using straw and inorganic fertilizers. The experiment was arranged using split plot design where rice straw as main plot and potassium fertilizer as subplot. The variable observed was agronomic variable, potassium uptake, exchangeable potassium. The straw incorporation into soil increased the higher exchangeable potassium content in topsoil and also could reduce K losses due to leaching. The peak of K uptake was occurred at panicle initiation growth phase and gradually declined at reproductive growth phase. Interaction between rice straw and potassium fertilization increased significantly grain yield of 0.93 – 1.39 t/ha. The increase of potassium rate and its application method did not influence significantly grain yield of Ciherang variety.